KATANIN 1 Is Essential for Embryogenesis and Seed Formation in Arabidopsis - Luptovčiak, Ivan; Samakovli, Despina; Komis, George; Šamaj, Jozef (Frontiers in Plant Science, 2017)
Cytoskeletal remodeling has a fundamental role, especially during transitional developmental stages when cells rapidly adopt new forms and roles, like gametogenesis, fertilization and concomitant embryogenesis and seed formation. KATANIN 1, a microtubule severing protein, fulfills a major regulatory mechanism of dynamic microtubule turnover in eukaryotes. Herein, we show that three well-established KATANIN 1 mutants, fra2, lue1 and ktn1-2 collectively display lower fertility and seed set in Arabidopsis. These lower fertility and seed set rates of fra2, lue1 and ktn1-2 mutants were correlated to abnormalities in the development of embryo proper and seed. Such phenotypes were rescued by transformation of mutants with functional pKTN1::GFP:KTN1 construct. This study significantly expands the already broad functional repertoire of KATANIN 1 and unravels its new role in embryo and seed development. Thus, KATANIN 1 significantly contributes to the fertility and proper embryo and seed formation in Arabidopsis.